German Economy Spring 2022 - Recovery at risk: Soaring inflation - Martin Ademmer; Jens Boysen-Hogrefe; Dominik Groll; Nils Jannsen; Stefan Kooths; Saskia Meuchelböck; Nils Sonnenberg (Kiel Institute for the World Economy (IfW Kiel), 2022)
The German economy is once again facing strong headwinds. The war in Ukraine is leading to a surge in commodity prices, additional supply bottlenecks and dwindling sales opportunities. These factors are hitting the economy in a phase in which the dampening effects of the pandemic are fading out and a strong recovery has begun to emerge. Higher commodity prices reduce the purchasing power of disposable incomes and thus dampen private consumption, while new supply bottlenecks will weigh on industrial production in the coming months. At the same time, sales opportunities deteriorate at least temporarily due to the sanctions and the uncertainty caused by the war. The negative effects, however, are cushioned because private households have accumulated large amounts of extra savings since the beginning of the pandemic, softening the blow to private consumption caused by higher inflation. In addition, manufacturing firms have an unusually high stock of orders, which will buffer lower sales opportunities. As a result, the recovery is likely to continue this year, albeit at a noticeably slower pace than previously expected. Overall, we expect GDP to rise by 2.1 percent this year (winter forecast: 4 percent) and by 3.5 percent in 2023 (winter forecast: 3.3 percent). At 5.8 percent, inflation is likely to be higher this year than ever before in reunified Germany. Even if commodity prices stop rising and supply bottlenecks gradually ease, inflation is still likely to be unusually high at 3.4 percent next year, also because recent producer price increases are only gradually being passed through to consumers. The labor market is expected to remain robust. Public spending will rise in response to the war and its economic consequences, so that budget deficits will remain at elevated levels for a longer period.
Keywords: 330